Inflamação pós-prandial: efeito de diferentes carboidratos dietéticos - Milene Cristina do Carmo Santos (2011)
Recent studies have suggested the occurrence of pulsatile inflammatory response at systemic levels during the feeding/fasting cycle that can be responsive to different dietary compositions. This study aimed to assess whether fed animals have postprandial systemic inflammation and determine if epididymal adipose tissue, liver or intestine could be sites of such inflammation. Furthermore, it was our goal to evaluate different dietary carbohydrates on postprandial response. For that, BALB/c mice were fasted or fed with AIN93 control diet, diet containing sucrose (C), or modified diet containing glucose (G) or fructose (F). The animals were killed at fasted state or one, two and four hours postprandial. Serum concentrations of PTX3, adiponectin and resistin, as well as cytokines and chemokine in the gut, liver and adipose tissue were determined by ELISA. Total and differential count of blood cells was also done. Increased serum of PTX3 levels were observed at four hours postprandial in animals fed with C, however, animals fed with G or F had this response anticipated. Animals fed C diet had high number of systemic leukocytes at four hours postprandial, yet consumption of G and F, once more, anticipated this effect. Independent of the consumed diet the concentration of resistin was increased and, animals fed G or F, had lower levels of adiponectin. In the postprandial period, independently of the diet composition, the concentration of IL-6 in adipose tissue and TNF- in the liver was increased. Animals fed C or G diet had similar neutrophil numbers in the liver when compared to animas in a fasted state, while animals fed with F had increased of neutrophils at all postprandial periods. In the gut, although the number of neutrophils was increased after the consumption of all diets, the concentration of TNF, IL-6 and KC was not detected. Animals in the fed state present low-level systemic inflammation that can be associated with specific metabolic sites as adipose tissue and liver. Different dietary compositions may influence this response, since animals fed fructose presented exacerbation of postprandial response.